1973
DOI: 10.1111/j.1432-1033.1973.tb02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Behaviour of Phosvitin

Abstract: The results of spectroscopic and microcalorimetric measurements on dilute aqueous solutions of phosvitin are described. Our infrared and circular dichroism spectra show that the phosphoprotein chains may assume either random-coiled or partially helical or /?-structures depending upon the pH. The transition to the low p H 8-form occurs with a distinct cooperative character.The strongly interdependent ionization of fixed charges densely spaced along phosvitin chains, typical of highly charged polyelectrolytes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…More than half of the amino acid residues are O-phosphoserine (Allerton & Perlmann, 1965). This produces a very high negative charge density along the chain, and the physico-chemical properties of the molecule are essentially those of a polyanion (Giancotti et al, 1973). Taborsky (1970) and Yoshimura et al (1979) showed that phosvitin formed a stable complex with cytochrome c that could be detectedby ultracentrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the amino acid residues are O-phosphoserine (Allerton & Perlmann, 1965). This produces a very high negative charge density along the chain, and the physico-chemical properties of the molecule are essentially those of a polyanion (Giancotti et al, 1973). Taborsky (1970) and Yoshimura et al (1979) showed that phosvitin formed a stable complex with cytochrome c that could be detectedby ultracentrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Interesting recent studies were recently reported on α-helical membrane lytic peptides, in which a few L-amino acids were replaced with their D-enantiomers: incremented amide I' frequencies (1656-1670 cm −1 ) compared with pure α-helical structures (1645-1654 cm −1 ) were observed and assigned to 3 10 -helix or dynamic/distorted α-helix (Papo and Shai, 2004). Previous studies had correlated this region with 3 10 -helix (Kennedy et al 1991), β-turn (Susi and Byler, 1986) and interestingly to a left-handed α-helix, as well (Giancotti et al 1973;Citra and Alxelsen, 1996). In this analysis two components around the typical region of helix absorption, centred at 1654 cm −1 and 1664 cm −1 , respectively (data not shown) were found ( Fig.…”
Section: Fourier-transformed Infrared Spectroscopy Experimentsmentioning
confidence: 87%
“…In contrast, acridine orange binds with K d % 0.87 mM (Table 1) (33), although all three dyes are known to bind DNA with high affinity (34). This remarkable difference and their different optical properties on polyelectrolyte binding (35) suggest that the binding of these cationic dyes to different polyanions follows different mechanisms. It is thus of future interest to clarify whether the pronounced difference in GAG binding is also the basis of their different biological uptake behavior, i.e., no membrane passage for ethidium and propidium (17) but rapid uptake and accumulation of acridine orange in endosomes (18,36).…”
Section: Binding Affinitymentioning
confidence: 98%